Internalisasi Nilai-Nilai Al-Qur’an melalui Program KKN Tematik pada Santri TPA Baitul Hasanah Desa Luan Sorip Kecamatan Simeulue Tengah Kabupaten Simeulue Provinsi Aceh - Lefantri , Leo; Hafitz, Hafitz; Abrar, Muhammad; Rizkiansyah , Rikaz; R, Mhd. Randa Haikal; Zamzamil, Mhd. Madil; Putra, Wahyu Hanafi (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
The formation of Qur’anic character from an early age is a noble ideal in Islamic education, pursued by educators, parents, and religious institutions alike. This research uses a qualitative approach with a descriptive method, aiming to explore the role of a thematic Community Service Program (Kuliah Kerja Nyata Tematik/KKNT) in strengthening Qur’anic values among children at TPA Baitul Hasanah in Luan Sorip Village, Central Simeulue District, Simeulue Regency, Aceh Province. Data were collected through observation, interviews, and documentation, involving students, teachers, and local community figures, and analyzed using the Miles and Huberman interactive model. The findings reveal that despite limited teaching resources and traditional learning methods, the implementation of a contextual and participatory teaching model—emphasizing affective, cognitive, and spiritual aspects—significantly enhanced the children’s Qur’an reading skills and their understanding of its moral values. The program fostered a lively and engaging learning atmosphere, supported by community collaboration and creative activities. It concludes that thematic community service programs can play a pivotal role in revitalizing Islamic education in rural areas by integrating academic knowledge with real-world community engagement.